HUBUNGAN KEBIASAAN MEROKOK DENGAN TITER IgA-EBV DIANTARA ORANG SEHAT - , BENNY HERMAWAN; , Jajah Fachiroh, S.P., M.Si., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BACKGROUND: Epstein Barr Virus (EBV) infects more than 90% of the world population and is classified as oncogenic virus. EBV is associated with various epithelial and lymphoid malignancies including nasopharyngeal carcinoma (NPC). NPC is a rare malignancy throughout most of the world, however a high incidence rate of NPC is well documented in Southeast Asia and Southern China. NPC was classified by World Health Organization (WHO) into 3 types, where type 3 is the most common and strongly associated with EBV infection. Reactivation of EBV is reflected by IgA-EBV response and can be used as specific biomarker for NPC. High IgA-EBV is detected in NPC patients, but high IgAEBV also detected in haelthy individual and may be a risk factor of NPC. Smoking is known to be associated with high levels of IgA-EBV. OBJECTIVE: To observe the association between smoking and IgA-EBV titres on healthy people . METHOD: A Cross sectional design is used in this study. 279 donors at PMI Kodya Yogyakarta and Sleman was included and given questionnaire about demographic data and smoking habits. Blood samples were collected and tested for IgA-EBV using indirect ELISA method. Association between smoking habits and IgA-EBV titres was analyzed using logistic regression with and without adjustment of age and education. RESULT: In total, 56 subjects (20,07%) have IgA-EBV titres above the cut-off value (0,35). Women was not included in this analysis because of the insufficient number of subjects. Ever smoker is associated with high level of IgA-EBV in men (OR=2,023